2000
DOI: 10.1080/14628830050516542
|View full text |Cite
|
Sign up to set email alerts
|

Selective non-ablative wrinkle reduction by laser

Abstract: In conclusion, the treatment modality described may be a new approach to the treatment of wrinkles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
4
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(145 citation statements)
references
References 13 publications
3
135
4
3
Order By: Relevance
“…There is also direct stimulation of fibroblasts by laser energy to produce more collagen. Bjerring et al 5 suggested that inflammatory mediators released from vascular endothelial cells damaged by the laser might cause new dermal collagen production by fibroblasts. There is also some nonspecific thermal damage from the scattering effect from both lasers that was seen in several biopsy specimens taken during the present evaluation.…”
Section: Commentmentioning
confidence: 99%
“…There is also direct stimulation of fibroblasts by laser energy to produce more collagen. Bjerring et al 5 suggested that inflammatory mediators released from vascular endothelial cells damaged by the laser might cause new dermal collagen production by fibroblasts. There is also some nonspecific thermal damage from the scattering effect from both lasers that was seen in several biopsy specimens taken during the present evaluation.…”
Section: Commentmentioning
confidence: 99%
“…[5][6][7][8][9] Thus, over time, one can see a remodeling of the photodamaged skin to give an improved histological and clinical result. 5,9 Heat can also have specific effects on collagen, the most abundant protein in the dermis. Studies indicate that collagen fibrils, when heated to the correct temperature over a period of time, will contract, which may lead to the rise in tissue tightening due to the breakage of the intramolecular hydrogen bonds.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Treatment regimens ranged from a single procedure 6 to 8 treatments at 2-to 3-week intervals. 11 In 10 of the trials, the clinical end point consisted of observation only.…”
Section: Resultsmentioning
confidence: 99%